Lunch eating habits in Portuguese college students considering the location of meal - Azevedo, Andreia (2014)
Introduction A healthy diet is associated with indicators of proximity to family, colleagues and school, and a perception of personal and social well-being. Objective To understand the eating habits of undergraduate higher education students, considering the location of meal. Methods A cross-sectional, quantitative study was developed using a probabilistic sample of 405 students from a Portuguese public higher education institution. Data collection involved the use of a questionnaire that included questions about the meal location, the type of meal, food/ingredients and their portion sizes. To verify if the consumption of different food groups, at lunch varies given the location where the meal was consumed, it was used the Kruskal-Wallis test. Results At lunch, significant differences were found in what concerns the consumption, being higher in cereals, cereal products and tubers, at "home", "school canteen" and "restaurant"; milk and derivatives in "other places"; oils and fats in the "restaurant"; candy in "restaurant"; fats in the "school canteen", "restaurant" and "other places"; and, juices in "other places". Conclusions These results suggest that higher education students eating habits vary according to the location of meal, only in some food groups. Regarding the consumption of fruits, vegetables, meat, fish and eggs, legumes, alcohol and salty there were no statistically significant differences, which suggests that the consumption of these foods is independent from the meal location.